Effect of Tactical Performance Endurance Exercise on the Level of the Hormones ANP-BNP for Young Football Players - Mukhald Bejai Attieh; Habeeb Ali Taher; Ahmed Murtda Abid AlHussain (Institute of Medico-legal Publications Pvt Ltd, 2021)
As for the objectives of the research, they were to prepare exercises that endure the planned performance at the level of the hormones ANP-BNP for young football players, and to identify the effect of exercises to endure the planned performance on the level of the hormones ANP-BNP for young football players, as well as to identify the preference for the effect between the control and experimental groups. Whereas the research hypotheses were that there was an effect of exercises to endure the planned performance on the level of the hormones ANP-BNP for young football players, there were also significant differences of statistical significance in favor of the experimental group in the post-tests. The researchers used the experimental approach in the manner of the two groups equivalent to the pre and post-test for suitability to the research variables. The study research community included the young football players for the clubs of the Holy Kerbala Governorate for the 2019/2020 sports season and its number (10) clubs by (220) players. The research sample was chosen randomly (drawing lots). The selection fell on the players of the Al-Ghariya Sports Club.